2021
DOI: 10.1029/2021gl093746
|View full text |Cite
|
Sign up to set email alerts
|

Sweeping Effects Modify Taylor’s Frozen Turbulence Hypothesis for Scalars in the Roughness Sublayer

Abstract: Elliptic Approximation (EA) for space-time correlations explored for scalar turbulence within the roughness sublayer of canopies • Advection velocity of eddies is commensurate with the mean streamwise velocity • Squared sweeping velocity obtained via EA scales linearly with measured turbulent kinetic energy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…For example, Everard et al . (2021) showed that in canopy flows (in their study zfalse/h$$ z/h $$ varied between 0.2 and 2) Uadv$$ {U}_{\mathrm{adv}} $$ was a constant fraction of local mean wind speed at all observation heights, indicative that Uadv$$ {U}_{\mathrm{adv}} $$ increased with height (since wind speed increases with height). Their findings are in qualitative agreement with other Uadv$$ {U}_{\mathrm{adv}} $$ profiles for sparse canopies (Huang et al, 2009).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…For example, Everard et al . (2021) showed that in canopy flows (in their study zfalse/h$$ z/h $$ varied between 0.2 and 2) Uadv$$ {U}_{\mathrm{adv}} $$ was a constant fraction of local mean wind speed at all observation heights, indicative that Uadv$$ {U}_{\mathrm{adv}} $$ increased with height (since wind speed increases with height). Their findings are in qualitative agreement with other Uadv$$ {U}_{\mathrm{adv}} $$ profiles for sparse canopies (Huang et al, 2009).…”
Section: Resultsmentioning
confidence: 95%
“…In such conditions, θ$$ \theta $$ isolines fluctuate vertically over the whole subcanopy domain, whereas Lw$$ {L}_w $$ may be affected by canopy elements breaking turbulent eddies and thus decreasing Lw$$ {L}_w $$. Third, there are large uncertainties in utilizing Taylor's frozen turbulence hypothesis in canopy flows (Huang et al, 2009; Brunet, 2020; Everard et al, 2021). Hence, estimating the integral length scale of w$$ w $$ from time series using a mean advection velocity become problematic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2009; Everard et al. 2021). It could be possible that the discrepancy between the two scalings for the counter-gradient quadrants is a result of the failure of Taylor's hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…Contrarily, for ejections and sweeps, this difference is insignificant. While converting Γ w to a length scale, Taylor's hypothesis is needed, which often is questionable in canopy turbulence (Finnigan et al 2009;Everard et al 2021). It could be possible that the discrepancy between the two scalings for the counter-gradient quadrants is a result of the failure of Taylor's hypothesis.…”
Section: An Alternative Scaling With Integral Scalesmentioning
confidence: 99%